Enseñanza de los fundamentos técnicos ofensivos del baloncesto en niños de 9 a 12 años del club deportivo Maes sport (sede la patria), en la ciudad de Armenia, Quindío (2015)
the work of internship, which goes by the name: strengthening the technical fundamentals of basketball in children from 9 to 12 years of club deportivo MAES sport (headquarters of the homeland), in the city of Armenia, Quindio, had as its main objective: "implement a proposal for strengthening the technical basketball in children 9 to 12 years in the sport club MAES headquarters the homeland, in the city of Armenia, in the department of Quindio." which was carried out in the club already mentioned with thirty (30) children ages nine (9) and twelve (12) years; this work recognizes the basketball as a sport propellant of cognitive processes, psychomotor, affective and social in its practitioners. For this reason, it led to encourage its good practice from the pedagogy as coadyuvador the teaching-learning process.